1997
DOI: 10.1212/wnl.49.5.1439
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic orthostatic tremor in pontine lesions

Abstract: Orthostatic tremor (OT) is a rare movement disorder that consists of involuntary shaking of the legs and trunk present only on standing. Although the origin and the mechanism of this condition are not well understood, the neurophysiologic abnormalities and PET studies suggest a central origin. We describe the clinical and radiologic features of two patients with symptomatic OT and associated pontine lesions, and conclude that OT may arise from dysfunction of the cerebellum or related pontine structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 4 publications
1
56
0
Order By: Relevance
“…20 In addition, OT associated with a pontine lesion was described. 7 Recently, 2 patients with OT after head trauma were described. 10,11 However, not all of these patients had typical OT as some of them displayed a lower frequency than the typical 14 to 18 Hz bursts (for example, Cases 7 and 8 in Gabellini and colleagues, 1990; Case 1 in Benito-Leon and coworkers, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 In addition, OT associated with a pontine lesion was described. 7 Recently, 2 patients with OT after head trauma were described. 10,11 However, not all of these patients had typical OT as some of them displayed a lower frequency than the typical 14 to 18 Hz bursts (for example, Cases 7 and 8 in Gabellini and colleagues, 1990; Case 1 in Benito-Leon and coworkers, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been rare reports of patients in whom OT was associated with other features, for instance, postural tremor of the arms 1-4 and Parkinson's disease (PD). 5,6 Also, OT has rarely been described in patients with pontine lesions, 7 cerebellar degeneration, 8,9 or after head trauma. 10,11 These reports could be considered forms of symptomatic OT.…”
mentioning
confidence: 99%
“…1 b). Symptomatic OT in patient B caused by a small unilateral cerebellar lesion seems unlikely although cerebellar dysfunction and pontine lesions have been described [4,5]. In both patients the imaging of striatal DAT ([ 123 I]FP-CIT-SPECT) and dopamine D 2 /D 3 receptors ([ 123 I]IBZM-SPECT), performed as described previously [15], showed ratios for specific uptake well within the range of healthy subjects indicating normal function of nigrostriatal dopaminergic systems.…”
Section: Florianmentioning
confidence: 98%
“…OT has been suggested to arise from a central oscillator involving the brainstem or cerebellum [4][5][6][7]. Interestingly, neuropathological changes in essential tremor have also been found in brainstem and cerebellar structures [8].…”
mentioning
confidence: 99%
“…Neurological examination re-OT is a rare clinical syndrome in which a rapid (14-16 Hz) regular lower limb tremor causes unsteadiness on standing that is relieved when sitting or walking. OT is generally considered to be an idiopathic disorder (primary OT), although it has also been described in patients with Parkinson's disease, hydrocephalus, pontine lesions, head trauma and cerebellar degeneration [4][5][6] . A positron emission tomography study in primary OT suggested increased blood fl ow in the cerebellum bilaterally and in the thalamus and lentiform nuclei contralateral to an arm with 16-Hz tremor, suggesting involvement of the cerebellum [7] .…”
Section: Case Reportmentioning
confidence: 99%